Designing a carbon nanotubes-interconnected ZIF-derived cobalt sulfide hybrid nanocage for supercapacitors. Issue 4 (6th December 2018) - Jian, Siou-Ling; Hsiao, Li-Yin; Yeh, Min-Hsin; Ho, Kuo-Chuan
Abstract : A hybrid structure of a cobalt sulphide nanocage derived from ZIF-67 and interconnected by CNTs is proposed as an electrode material for SCs. Abstract : Owing to their advantages of high power density and a short charging duration, electrochemical supercapacitors (SCs) have received much attention as alternative energy systems for applications in portable electronic devices. The design of an electrode material with high capacitance and promising cycling stability will be a key factor for promoting the development of SC-based electronic systems. In this study, a hybrid structure of a cobalt sulfide nanocage derived from a zeolitic imidazolate framework (ZIF) and interconnected by carbon nanotubes (CNT/CoS) was designed and synthesized as an electrode material for SCs. Carbon nanotubes/ZIF-67 (CNT/ZIF-67) nanocomposites with controlled ZIF-67 particle sizes were systematically studied by varying the mass ratio of CNTs to ZIF-67 during crystallization, followed by subsequent sulfurization with thioacetamide. Benefiting from the porous nanocage architecture and conductive CNTs, the optimized CNT/CoS nanocage exhibited excellent electrochemical performance with an outstanding specific capacitance (2173.1 F g −1 at 5 A g −1 ) and high rate capability (65% retention at 20 A g −1 ). More importantly, a symmetric supercapacitor gave an energy density of 23.3 W h kg −1 at a power density of 3382.2 W kg −1 and impressive long-term stability (96.6% retention after 5000 cycles). These results suggest that the CNT/CoS nanocage is a promising composite for high-performance supercapacitor applications.